Design, synthesis, in vitro and in vivo evaluation of benzylpiperidine-linked 1,3-dimethylbenzimidazolinones as cholinesterase inhibitors against Alzheimer's disease - Jun Mo; Tingkai Chen; Hongyu Yang; Yan Guo; Qi Li; Yuting Qiao; Hongzhi Lin; Feng Feng; Wenyuan Liu; Yao Chen; Zongliang Liu; Haopeng Sun (Taylor & Francis Group, 2020)
Cholinesterase inhibitor plays an important role in the treatment of patients with Alzheimer's disease (AD). Herein, we report the medicinal chemistry efforts leading to a new series of 1,3-dimethylbenzimidazolinone derivatives. Among the synthesised compounds, 15b and 15j showed submicromolar IC50 values (15b, eeAChE IC50 = 0.39 ± 0.11 µM; 15j, eqBChE IC50 = 0.16 ± 0.04 µM) towards acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Kinetic and molecular modelling studies revealed that 15b and 15j act in a competitive manner. 15b and 15j showed neuroprotective effect against H2O2-induced oxidative damage on PC12 cells. This effect was further supported by their antioxidant activity determined in a DPPH assay in vitro. Morris water maze test confirmed the memory amelioration effect of the two compounds in a scopolamine-induced mouse model. Moreover, the hepatotoxicity of 15b and 15j was lower than tacrine. In summary, these data suggest 15b and 15j are promising multifunctional agents against AD.